2019
DOI: 10.1111/mmi.14219
|View full text |Cite
|
Sign up to set email alerts
|

The meiosis‐specific APC activator FgAMA1 is dispensable for meiosis but important for ascosporogenesis in Fusarium graminearum

Abstract: Ascospores are the primary inoculum in Fusarium graminearum . Interestingly, 70 of its genes have premature stop codons (PSC) and require A-to-I editing during sexual reproduction to encode full-length proteins, including the ortholog of yeast Ama1, a meiosis-specific activator of APC/C. In this study, we characterized the function of FgAMA1 and its PSC editing. FgAMA1 was specifically expressed during sexual reproduction. The Fgama1 mutant was normal in growth and perithecium formation but defective in ascosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…In a previous study, FgPAL1 (FGSG_08726) was found to be upregulated in the Fgama1 mutant and important for ascosporogenesis (Hao et al, 2019). FgPAL1 is orthologous to PAL1 of S. cerevisiae and encodes a 521 amino acid (aa) protein with a conserved PAL1 domain at the C-terminal region.…”
Section: Fgpal1 Is Important For Normal Tip Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, FgPAL1 (FGSG_08726) was found to be upregulated in the Fgama1 mutant and important for ascosporogenesis (Hao et al, 2019). FgPAL1 is orthologous to PAL1 of S. cerevisiae and encodes a 521 amino acid (aa) protein with a conserved PAL1 domain at the C-terminal region.…”
Section: Fgpal1 Is Important For Normal Tip Growthmentioning
confidence: 99%
“…Interestingly, 70 genes have premature stop codons (PSCs) that require A-to-I editing to encode full-length functional proteins in F. graminearum. Several genes with PSC editing events are known to be important for ascospore formation or release, including PUK1, AMD1 and FgAMA1 (Liu et al, 2016;Cao et al, 2017;Hao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pal1p was reported to be present at the initial stage of endocytosis to and interact with Ede1p, but was not required for bulk-or receptor-mediated endocytosis in S. cerevisiae (Carroll et al, 2012). In F. graminearum, deletion of FgPAL1 resulted in defects in fungal development, such as vegetative growth, perithecial formation and ascospore morphology (Hao et al, 2019). Although there have been studies in a few fungi, the function of Pal1 proteins is still largely unknown in fungal pathogens.…”
Section: Introductionmentioning
confidence: 99%